Expenditure Raises Income: An Empirical Analysis of Income and Expenditure - Hirani, Jhaman Das; Chandio, Rafiq Ahmed (Annals of Human and Social Sciences, 2024)
This paper intends to examine this relationship between municipal income and expenditure using ten-year data on four municipalities. Since, it is argued that municipalities spending raise their income. The Ordinary Least Square (OLS) regression and Fixed Effect Method (FEM) are used to verify this relationship. Furthermore, the municipal expenditures collectively and its components were tested individually against cumulative income and separate income components and vice versa. From all these testings and examination the results confirm that municipal expenditures have positive and significant effect on municipal income. With increase of each unit in municipal expesens the income also incrases. Similary, panel estimates indicate that a one percent increase in the expenditures results in more than one percent increase in municipal income. Based on both time series and panel estimates, it is recommended to identify rewarding municipal services and spend upon such services to increase local income.